The Influence Of Operating Costs On The Sensitivity Of Financial Viability Case Study: Construction Of South Surabaya Regional General Hospital - Rachma Damayanti; Andi Patriadi; Sajiyo Sajiyo (Journal of World Science, 2025)
This study evaluates the financial feasibility of constructing the South Surabaya Regional General Hospital using key investment evaluation methods, including Net Present Value (NPV), Internal Rate of Return (IRR), benefit-cost ratio (BCR), and Payback Period (PP). The study also examines how changes in management costs affect the project's financial viability. Data collected includes both initial investment costs and ongoing operational expenses. The findings indicate that the project is financially viable, with a positive NPV, an IRR higher than the required rate of return, and a payback period shorter than planned. Sensitivity analysis highlights that management costs significantly influence the project's feasibility. These insights can help the Surabaya City Government optimize hospital management costs and ensure the sustainability of healthcare projects.